mRNA expression profile of serotonin receptor subtypes and distribution of serotonergic terminations in marmoset brain - Shukla, Rammohan; Watakabe, Akiya; Yamamori, Tetsuo (Frontiers in Neural Circuits, 2014)
To better understand serotonin function in the primate brain, we examined the mRNA expression patterns of all the 13 members of the serotonin receptor (5HTR) family, by in situ hybridization and the distribution of serotonergic terminations by serotonin transporter (SERT) protein immunohistochemical analysis. Ten of the 13 5HTRs showed significant mRNA expressions in the marmoset brain. Our study shows several new features of the organization of serotonergic systems in the marmoset brain. (1) The thalamus expressed only a limited number of receptor subtypes compared with the cortex, hippocampus, and other subcortical regions. (2) In the cortex, there are layer-selective and area-selective mRNA expressions of 5HTRs. (3) Highly localized mRNA expressions of 5HT1F and 5HT3A were observed. (4) There was a conspicuous overlap of the mRNA expressions of receptor subtypes known to have somatodendritic localization of receptor proteins with dense serotonergic terminations in the visual cortex, the central lateral nucleus of the thalamus, the presubiculum, and the medial mammillary nucleus of the hypothalamus. This suggests a high correlation between serotonin availability and receptor expression at these locations. (5) The 5HTRs show differences in mRNA expression pattern between the marmoset and mouse cortices whereas the patterns of both the species were much similar in the hippocampus. We discuss the possible roles of 5HTRs in the marmoset brain revealed by the analysis of their overall mRNA expression patterns.